Interactive stability of multiobjective NLP problems with fuzzy parameters in the objective functions and constraints - Ammar, Elsaid Ibrahim (Fuzzy sets and systems, 2000)
This paper deals with an interactive stability of multiobjective nonlinear programming problems with fuzzy parameters in the objective functions and constraints. These fuzzy parameters are characterized by fuzzy numbers. The existing results concerning the qualitative analysis set of the first kind are reformulated to study this set under the concept of α-pareto optimality. An interactive algorithm for obtaining the α-best-compromise and obtaining any subset of the parametric space which has the same corresponding α-pareto optimal solution is also presented. An illustrative example is given.